Differences of in children’s motivation to brush their teeth using toothpaste and without toothpaste - Nengsih, Ade Sri (Padjadjaran Journal of Dentistry, 2013)
Introduction: Motivation to brushing teeth consists of intrinsic and extrinsic factor. Extrinsic factor is the most influence to chlid’s motivation. One of the extrinsic factor is toothpaste. The purpose of this study was to analyzed child’s motivation differences between using toothpaste and without toothpaste. Method: This applied descriptive comparative research was using single blind method, with a sample size of 62 preschool children at Sekeloa, ranged from 4 to 6 years old. sampling technique using total sampling. The variables in this study were child’s motivation and toothpaste. The tools and materials used in this study were motivation scale and tooth brushing activity sheets, informed consent, toothpaste, and toothbrushes.Result: The result shows that the highest motivational category on children who using toothpaste are 8 students (25,81%), while on children without toothpaste are 3 students (9,68%). Base on statistical analysis shows that a large motivational differences between children group using toothpaste and without toothpaste. Conclusion: There is a differences motivation between children that brush their teeth using toothpaste without toothpaste.